(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
It explores three prominent conceptualizations that are component of the assessment of commercial surrogacy, including the commercialization of parenthood, the eroticism of the gift correlation, and the organization of the surrogate, particularly in connection to the feminist as well as academic assessment of surrogacy in India, throughout this essay. Surrogacy continues to be influenced by powerful rhetorical ideals such as motherhood, autonomy, and the romanticism of the gift, all of which continue to affect the research and interpretation of surrogacy. They are solidified as the key structural settings inside which surrogacy appears to work as a result of this process. These three themes are examined in the article’s survey of modern published research on commercialized surrogacy, which examines the academic interactions with these three conceptions.